2006
DOI: 10.1111/j.1572-0241.2006.00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastroparesis: Clinical Update. CME

Abstract: Gastroparesis refers to chronically abnormal gastric motility characterized by symptoms suggestive of mechanical obstruction and delayed gastric emptying in the absence of mechanical obstruction. It may be idiopathic or attributable to neuropathic or myopathic abnormalities, such as diabetes mellitus, postvagotomy, postviral infection, and scleroderma. Dietary and behavioral modification, prokinetic drugs, and surgical interventions have been used in managing patients with gastroparesis. Although mild gastropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 102 publications
0
81
0
3
Order By: Relevance
“…5,6 Its pathogenesis has not been fully elucidated to date, 5,7 and the most common cause has been known to be idiopathic, including post-viral infection; diabetes and postsurgical complications are its other causes. 5,7 Its mechanisms include impaired gastric accommodation, antral hypomotility with pyloric spasm, duodenal dysmotility, among others.…”
Section: Diagnosis: Idiopathic Gastroparesismentioning
confidence: 99%
“…5,6 Its pathogenesis has not been fully elucidated to date, 5,7 and the most common cause has been known to be idiopathic, including post-viral infection; diabetes and postsurgical complications are its other causes. 5,7 Its mechanisms include impaired gastric accommodation, antral hypomotility with pyloric spasm, duodenal dysmotility, among others.…”
Section: Diagnosis: Idiopathic Gastroparesismentioning
confidence: 99%
“…5) and more rapidly than solids, with no lag phase. A previously held belief was that liquid GE added little to the evaluation of patients with dyspepsia (33,34). It was felt that since the liquids require no trituration, liquid GE remained normal until gastroparesis was at an advanced stage and that liquids were therefore less sensitive than solids for detecting early gastroparesis (35).…”
Section: Gastric Emptyingmentioning
confidence: 99%
“…Studies have shown these agents to increase gastric emptying by 25 to 75% and reduce the severity of symptoms by 25 to 68%. 10,11,12 When pain relief is required, tramadol and opiates should be avoided. These have inhibiting effects on motility.…”
Section: Managementmentioning
confidence: 99%